2011
DOI: 10.2139/ssrn.1821225
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Household Efficiency: An Experimental Study from Ethiopia

Abstract: An experimental design using treatments of a voluntary contribution mechanism is used to test household efficiency. Efficiency is decisively rejected in all treatments contrary to the assumption of most household models. Information on initial endowments of spouses improves efficiency only in some treatments suggesting that the impact of information is context dependent. Actual and expected contribution rates of spouses are systematically different; husbands' (wives') expectations of their wives' (husbands') c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 36 publications
4
17
0
Order By: Relevance
“…In other words, wives are more likely to keep and prioritize separate budgets than are husbands. Qualitatively similar results were reported by Kebede et al (2014) from experiments in Ethiopia involving various treatments in the form of voluntary contributions. They found that although both men and women chose to keep a portion of their endowments to themselves at the expense of household efficiency, in some of the treatments, men contributed more than women but the women never contributed more than the men in any of the treatments.…”
Section: Sharing Within Family: Allocation To Spousesupporting
confidence: 87%
“…In other words, wives are more likely to keep and prioritize separate budgets than are husbands. Qualitatively similar results were reported by Kebede et al (2014) from experiments in Ethiopia involving various treatments in the form of voluntary contributions. They found that although both men and women chose to keep a portion of their endowments to themselves at the expense of household efficiency, in some of the treatments, men contributed more than women but the women never contributed more than the men in any of the treatments.…”
Section: Sharing Within Family: Allocation To Spousesupporting
confidence: 87%
“…This between-subject analysis mimics those used previously in the experimental literature studying household behavior (e.g. Iversen et al (2013), Kebede et al (2014), Mani (2011)), and is analogous to between-subject field experiments (e.g. Ashraf (2009)) and natural experiments studied with cross-sectional surveys (e.g.…”
Section: Resultsmentioning
confidence: 83%
“…4 Bobonis (2009) and Attanasio and Lechene (2014) find in favor of efficiency in expenditure decisions in Mexico, while Duflo and Udry (2004) and Robinson (2012) find against efficiency in expenditures decisions in Cˆote d'Ivoire and Kenya respectively. Udry (1996) finds against efficiency in agricultural investment decisions in Burkina Faso, while Kebede et al (2014), Iversen et al (2011), and Mani (2011) reject productive efficiency in laboratory games played between spouses in Ethiopia, Uganda, and India respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations